2011
DOI: 10.1007/s00280-011-1665-1
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate toxicity and efficacy during the consolidation phase in paediatric acute lymphoblastic leukaemia and MTHFR polymorphisms as pharmacogenetic determinants

Abstract: Our study provides further evidence of the critical role played by folate pathway enzymes in the outcome of ALL, possibly through the interference of MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 23 publications
2
33
2
Order By: Relevance
“…An earlier similar study showed patients with the MTHFR 677CC genotype had a trend of longer TTP (but not response) to cisplatin/gemcitabine in Stage IV NSCLC (Alberola et al, 2004). Other recent reports showed that acute lymphoblastic leukaemia (ALL) patients with 677TT genotype had a significantly higher incidence of relapse compared to other genotypes after the consolidation methotrexate therapy (D′Angelo et al, 2011;Salazar et al, 2011). However, other studies showed MTHFR 677T allele carriers had a higher response rate to 5-FU-based chemotherapy (Cohen et al, 2003;Fernández-Peralta et al, 2010) or FOLFOX therapy (Etienne-Grimaldi et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…An earlier similar study showed patients with the MTHFR 677CC genotype had a trend of longer TTP (but not response) to cisplatin/gemcitabine in Stage IV NSCLC (Alberola et al, 2004). Other recent reports showed that acute lymphoblastic leukaemia (ALL) patients with 677TT genotype had a significantly higher incidence of relapse compared to other genotypes after the consolidation methotrexate therapy (D′Angelo et al, 2011;Salazar et al, 2011). However, other studies showed MTHFR 677T allele carriers had a higher response rate to 5-FU-based chemotherapy (Cohen et al, 2003;Fernández-Peralta et al, 2010) or FOLFOX therapy (Etienne-Grimaldi et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…They observed that patients with 5 g/m 2 MTX had a lower frequency of suffering an event than that the patients treated with 3 g/ m 2 MTX (677C+1298A vs. 677 T+1298C, P=0.012) in the consolidation phase. However, D'Angelo et al [72] did not find any difference between 2 and 5 g/m 2 MTX during consolidation phase.…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 97%
“…Therefore, patients with decreased MTHFR activity are at an increased risk of MTX-related toxicity. The analysis shows that patients with 677TT genotype had a 13 fold increased risk of developing non-hahematological toxicity in the 2 gram MTX dose subgroup when compared to other genotypes and doses [5].…”
Section: Mthfrmentioning
confidence: 99%